Selection of kindergarten the parents / Nurul Faizah Hamzah and Masturah Bakhari - Hamzah, Nurul Faizah; Bakhari, Masturah (2006)
Kindergarten is the place for the children around the age of four to six years are given an early exposure on the education. The kindergarten nowadays being the important element due to the awareness of the parent towards the child's education. Kindergarten is the first stage of the education for the child and it is the preparation session before entering the primary school.